2021
DOI: 10.1001/jamanetworkopen.2021.31490
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Electronic Health Record Inbox Messaging During the COVID-19 Pandemic in an Ambulatory Practice Network in New England

Abstract: were grouped into primary care, medical, and surgical specialties (eTable 2 in the Supplement).Variables were compared before (March 2018 to February 2020) and during (March 2020 to June 2021) the COVID-19 pandemic. To assess whether the onset of the pandemic was an inflection point in PMARs, message volume per physician per day was modeled by piecewise linear regression using a spline for month with a single knot at March 2020 and Huber-White SEs. Three months of inbox message data were missing (3 of 40 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 6 publications
1
62
0
Order By: Relevance
“…We observed similar dynamic patterns in PGMs on COVID-19, particularly, COVID-19 diagnosis and treatment, suggesting that patients actively used the portal messaging for addressing their concerns regarding the COVID-19 crisis [ 23 ]. Another previous study [ 26 ] was consistent with our findings, as they analyzed messages in an ambulatory practice network and determined that their inbox message usage patterns were also consistent with national trends. Patients sent portal messages mainly for COVID-19 symptom self-assessment and discussing COVID-19 tests and results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed similar dynamic patterns in PGMs on COVID-19, particularly, COVID-19 diagnosis and treatment, suggesting that patients actively used the portal messaging for addressing their concerns regarding the COVID-19 crisis [ 23 ]. Another previous study [ 26 ] was consistent with our findings, as they analyzed messages in an ambulatory practice network and determined that their inbox message usage patterns were also consistent with national trends. Patients sent portal messages mainly for COVID-19 symptom self-assessment and discussing COVID-19 tests and results.…”
Section: Discussionsupporting
confidence: 91%
“…Portz et al [ 25 ] observed a large increase of patient portal utilization for advance care planning. However, very few research studies examined the messaging component of the portal, an important function of patient portals for asynchronous communication between patients and providers, specifically for COVID-19–related care and issues [ 26 ]. Thus, in this study, we assessed portal messages associated with COVID-19 generated by patients from February 1 to August 31, 2020, at Mayo Clinic, a large multispecialty academic health system.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important given recent evidence identifying In-Basket messages in particular as a predictor of physician burnout, as well as other studies finding a significant increase in patient messages received by clinicians during the pandemic. 12 , 15 , 35 Policymakers and health system leaders should keep these new demands on clinician time in mind as they develop future reimbursement models and workflows, taking care not to exacerbate EHR-driven clinician burnout. 18 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…This is unsurprising given the substantial baseline number of inbox type messages PCPs receive, which has risen even further during the COVID-19 pandemic. 19 This frequently led to incomplete responses to requests from ADCs. Other research in home and community-based services validates this.…”
Section: Discussionmentioning
confidence: 99%